The Relationship of Upper Arm Muscle Strength and Eye-Hand Coordination with The Effectiveness of The Bottom Service - Nugraha, Faisal Prasetya; Warthadi , Anugrah Nur; Jariono, Gatot (Universitas PGRI Palembang, 2025)
Sport is defined as a form of planned, gradual and continuous sports activity to improve the athlete's ability through competition. Sport does not pay attention to race, religion or ethnicity, because sport can unite people and help them become better. Volleyball is one of the sports that is quite popular in Indonesia. Volleyball has the advantage that playing it does not require a lot of money, so it becomes a special attraction especially at SDN Sondakan by holding a volleyball tournament. In participating in the volleyball tournament, SDN Sondakan has never won, so in extracurricular activities it is necessary to improve the achievements and training of its students. An athlete must be in good physical condition in order to play volleyball well. Eye and hand coordination needs to be done to improve the use of the hands when serving. Arm muscle strength also affects an athlete's ability to serve underhand.This research aims to determine the relationship between upper arm muscle strength and eye-hand coordination with the effectiveness of the bottom serve in volleyball at SDN Sondakan in 2024. The research method used is a quantitative research method with correlational tests. The population in this study were extracurricular boys' volleyball students at SDN Sondakan. The sample taken from the total sampling results was 10 students. Data collection techniques use tests and measurements. The background of the problem in this research is.1) It is not yet known whether there is a relationship between upper arm muscle strength and the effectiveness of volleyball underhand service.2) It is not yet known whether there is a relationship between eye-hand coordination and the effectiveness of volleyball underhand serves.3) It is not yet known whether there is a relationship between upper arm muscle strength and eye-hand coordination with the effectiveness of volleyball underhand serves. The aim of this research is 1) Knowing the relationship between arm muscle strength and the effectiveness of volleyball underhand serve. 2) Knowing the relationship between eye-hand coordination and the effectiveness of volleyball underhand service.3) Knowing the relationship between eye-hand coordination and the effectiveness of volleyball underhand service..The data analysis technique used is statistical analysis through correlation studies. The research results obtained, 1) There is a relationship between upper arm muscle strength and the effectiveness of the lower serve in men's volleyball at SDN Sondakan, with a value of rcount = 0.849 > rtable = 0.631; 2) there is a significant relationship between hand-eye coordination and the effectiveness of the bottom serve with a value of rcount = 0.641 > rtable = 0.631; 3) there is a relationship between arm muscle strength and eye-hand coordination with the effectiveness of the bottom serve with a value of rcount = 0.804 > rtable = 0.631. The conclusion is that upper arm muscle strength and hand-eye coordination are significantly related to the effectiveness of the volleyball bottom serve.